1987
DOI: 10.1080/17450398709425344
|View full text |Cite
|
Sign up to set email alerts
|

Zum Einfluß Einer Hinsichtlich Qualität und Quantität Unterschiedlichen Proteinversorgung auf Wachstum und Wachstumshormon im Serum Entwöhnter Ratten

Abstract: A two-factorially experiment was done over a period of 42 days using 32 male, weaned Sprague-Dawley rats in order to study the effect of insufficient protein supplementation, with regard to quantity and quality (13% protein in comparison to 18%, and an essential amino acid index of 64 in comparison to 92%, resp.), on weight development and serum growth hormone concentration. Qualitative protein deficiency had a greater adverse effect on weight development and feed utilization than did quantitative protein defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
1994
1994

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…This means that the reduced GH concentrations in the serum of the Zn-deficient and the pair-fed control rats is the result of the reduced feed intake and the associated protein and energy depletion rather than being caused by Zn deficiency per se. Other authors also reported a marked influence of feed intake {Phillips and Young 1976; Ghavami-Maibodi, Collipp, Castro-Magana, Stewart and Chen 1983;Nishi, Hatano, Aihara, Fujie and Kihara 1989) or of energy and protein deficiency (Kirchgefiner, Jacob-Hammermann and Roth 1987;Jacob-Hammermann, Kirchgefiner and Roth 1987) on the GH concentration in the serum. In situations of marginal Zn depletion, when the rats' feed intake was unaffected or only slightly impaired (Kirchgefiner and Roth 1985), while the serum Zn concentrations were nonetheless significantly reduced, GH concentrations in the serum of the Zn-deficient rats were also distinctly reduced compared to the pair-fed control rats.…”
Section: Introductionmentioning
confidence: 93%
“…This means that the reduced GH concentrations in the serum of the Zn-deficient and the pair-fed control rats is the result of the reduced feed intake and the associated protein and energy depletion rather than being caused by Zn deficiency per se. Other authors also reported a marked influence of feed intake {Phillips and Young 1976; Ghavami-Maibodi, Collipp, Castro-Magana, Stewart and Chen 1983;Nishi, Hatano, Aihara, Fujie and Kihara 1989) or of energy and protein deficiency (Kirchgefiner, Jacob-Hammermann and Roth 1987;Jacob-Hammermann, Kirchgefiner and Roth 1987) on the GH concentration in the serum. In situations of marginal Zn depletion, when the rats' feed intake was unaffected or only slightly impaired (Kirchgefiner and Roth 1985), while the serum Zn concentrations were nonetheless significantly reduced, GH concentrations in the serum of the Zn-deficient rats were also distinctly reduced compared to the pair-fed control rats.…”
Section: Introductionmentioning
confidence: 93%